Changes: Reinventing the Graduation Ceremony: - Kuze, Ieva; Spengelis, Edgars (ICAReAlumni Conference Proceedings, 2020)
Background: Some people say we don't need to change things that already work. But others are willing to risk and jump forward. And this story is about changing the history and traditions at Riga Technical University (RTU). Reinventing. Until year 2017 RTU had more than 50 graduation ceremonies per year (separate for each faculty and institute). Needless to say, that it is very hard to get high rank administration (rector, deans etc.) to participate in all of them. And we're not even talking about the entertainment part — artists, who are making these graduation ceremonies even more worth remembering for alumni. So... we really wanted to not only optimize processes about graduation events, but also make them more convenient for all parties involved.